Study and experiment on the alternative technique of frequency–dependent squeezing generation with EPR entanglement for Virgo. (February 2020) - Bawaj, M; Barsuglia, M; Bazzan, M; Calloni, E; Ciani, G; Conti, L; D'Angelo, B; De Laurentis, M; De Rosa, R; Di Pace, S; Fafone, V; Garaventa, B; et al.
Abstract: In this paper, we summarize the present state-of-the-art on the proof-of-principle experiment of frequency-dependent squeezing implemented through EPR entanglement for Virgo gravitational-wave detector and we introduce Virgo subsystem proposal for frequency-dependent squeezing, obtained with a compact apparatus and without the costs required by the infrastructure for the filter cavity.